2019
DOI: 10.21577/0100-4042.20170409
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Perfil De Liberação Do Fármaco Ibuprofeno Em Membranas Simétricas E Assimétricas De Acetato De Celulose: Efeito Da Morfologia

Abstract: Recebido em 21/04/2019; aceito em 30/07/2019; publicado na web em 11/09/2019 EVALUATION OF THE IBUPROFEN DELYVERY PROFILE IN SYMMETRIC AND ASYMMETRIC MEMBRANES OF CELLULOSE ACETATE: EFFECT OF MORPHOLOGY. Cellulose derivatives still receive special attention in today biomedical applications due to their biocompatibility, ability to form resistant membranes and compatibility with various bioactive agents. In this work, cellulose acetate (CA) was used to prepare membranes with different morphologies aiming to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…E continued to increase up to ≈141 kJ mol −1 at 75% conversion ( = 0.75). Therefore, E values indicated an intense association of CA with both drugs, enabling an increase in thermal stability which can be attributed to the formation of hydrogen bonds between the carboxylic acid groups of the drugs and the free hydroxyls of CA, which is in agreement with the results reported by Ma et al [17] and Ferreira et al [13] Finally, the results showed both systems consist of good solid dispersions with well-distributed drugs. However, the calculated E values suggest the CA-NPX system has a stronger interaction established between the drug and the CA matrix relative to CA-IBF.…”
Section: Thermal Decomposition Assayssupporting
confidence: 90%
See 3 more Smart Citations
“…E continued to increase up to ≈141 kJ mol −1 at 75% conversion ( = 0.75). Therefore, E values indicated an intense association of CA with both drugs, enabling an increase in thermal stability which can be attributed to the formation of hydrogen bonds between the carboxylic acid groups of the drugs and the free hydroxyls of CA, which is in agreement with the results reported by Ma et al [17] and Ferreira et al [13] Finally, the results showed both systems consist of good solid dispersions with well-distributed drugs. However, the calculated E values suggest the CA-NPX system has a stronger interaction established between the drug and the CA matrix relative to CA-IBF.…”
Section: Thermal Decomposition Assayssupporting
confidence: 90%
“…TGA www.advancedsciencenews.com www.ms-journal.de Adapted from. [ 11,13] curves for IBF and NPX exhibited the main thermal events responsible for 100% of mass loss at a temperature of around 200 to 250°C, respectively. A major thermal event responsible for the degradation of CA is observed at 332°C with a mass loss of approximately 75%, while CA-drug membranes showed a mass loss of 65%, which is related to the thermal decomposition of the membrane's CA main chains at ∼328°C.…”
Section: Thermogravimetric Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Cellulose acetate (CA), in special, is a polymer widely used as a matrix for several applications including water purification and desalination, 18–20 gas separation, 21 drug release, 22 and sensor fabrications 23 . The vast applicability is essentially due to the low cost, low toxicity, and the ability to form films.…”
Section: Introductionmentioning
confidence: 99%